Perancangan dan Pembuatan Plasma Blood Separator Berbasis Arduino Uno - Patrisius Kusi Olla; Bayu Wahyudi; Muhammad Nur Alfian; Diah Rahayuningtyas; Mohammad Rofi'i (Jurnal Teori dan Aplikasi Fisika, 2025)
This research aims to design a Plasma Blood Separator that can separate plasma from red blood cells automatical-ly using an Optocoupler sensor and a specimen tube cutter. This sistem is equipped with an Arduino Uno as the con-trolling brain, a servo motor to clamp the hose, a DC motor to open the blood bag pressure, a series of push buttons to open the servo, and a buzzer to indicate the completion of separation. After testing the Arduino Uno-based Plasma Blood Separator, all functions can work well by showing results in three trials varying the length of the tube. The var-ied hose lengths are 38 cm, 52 cm, 71 cm. The estimated separation times are 1.16 minutes, 2.17 minutes and 3.4 minutes. In the voltage measurement results, the measurement results were obtained with a small percentage of error with a value of <5% and a high accuracy value with a value of >90%. Keywords: plasma blood, separator, arduino